2013
DOI: 10.1016/j.psyneuen.2013.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic regulation across phases of the menstrual cycle and sleep stages in women with premenstrual syndrome and healthy controls

Abstract: Summary To investigate the influence of menstrual cycle phase and the presence of severe premenstrual symptoms on cardiac autonomic control during sleep, we performed heart rate variability (HRV) analysis during stable non-rapid eye movement (NREM) and REM sleep in 12 women with severe premenstrual syndrome and 14 controls in the mid-follicular, mid-luteal, and late-luteal phases of the menstrual cycle. Heart rate was higher, along with lower high frequency (HF) power, reflecting reduced vagal activity, and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 47 publications
5
58
0
Order By: Relevance
“…Most studies based on short-duration ECG recordings found that there is a reduction in cardiac vagal activity and a shift to sympathetic dominance in the luteal phase compared with the follicular phase (see von Holzen et al, 2016, for review). We had similar findings based on recordings made during sleep in young healthy women in the mid-luteal phase relative to the follicular phase (de Zambotti et al, 2013c) and also showed that women with severe premenstrual syndrome had altered sleep-related HRV measures in response to the luteal phase compared with controls (Baker et al, 2008; de Zambotti et al, 2013c). HRV measures also change with age and in association with menopausal hormone changes: there is a reduction in vagal activity and a shift to sympathetic dominance that emerges one year after menopause, when estradiol levels are low (von Holzen et al, 2016).…”
Section: Introductionsupporting
confidence: 66%
“…Most studies based on short-duration ECG recordings found that there is a reduction in cardiac vagal activity and a shift to sympathetic dominance in the luteal phase compared with the follicular phase (see von Holzen et al, 2016, for review). We had similar findings based on recordings made during sleep in young healthy women in the mid-luteal phase relative to the follicular phase (de Zambotti et al, 2013c) and also showed that women with severe premenstrual syndrome had altered sleep-related HRV measures in response to the luteal phase compared with controls (Baker et al, 2008; de Zambotti et al, 2013c). HRV measures also change with age and in association with menopausal hormone changes: there is a reduction in vagal activity and a shift to sympathetic dominance that emerges one year after menopause, when estradiol levels are low (von Holzen et al, 2016).…”
Section: Introductionsupporting
confidence: 66%
“…Cajochen et al suggested that the observed rhythm in sleep variables represents a circalunar rhythm property, running in synchrony with the lunar phases, reminiscent of other endogenous rhythms such as the circadian and circannual rhythms [31]. In addition, as mentioned before, there is a strong link between female sex hormones and sleep [32], and female reproductive steroids appear to be involved in the cardiac autonomic control during sleep in women [59]. This implies the existence of sex differences in the structure of sleep, as well as in the association between lunar phases and sleep.…”
Section: Discussionmentioning
confidence: 92%
“…Estrogen levels reportedly have effects on the cardiovascular system and the autonomic nervous system, increasing parasympathetic and decreasing sympathetic activity (6). In contrast, progesterone reportedly correlated with the LF/HF ratio in both non-REM sleep and REM sleep and negatively correlated with HF power in non-REM sleep among non-PMS women (32). Sympathetic hyperactivity is associated with anxiety and mood disturbance (33).…”
Section: Discussionmentioning
confidence: 99%